RENEWABLE ENERGY FROM SOLAR PANELS: A STUDY OF PHOTOVOLTAIC PHYSICS AND ENVIRONMENTAL BENEFITS - Jaiswal, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper explores the role of solar energy as a transformative force in the global energy landscape, emphasizing its environmental, economic, and technological advantages. The study analyzes the current state of solar photovoltaic (PV) technology, highlighting significant trends such as declining costs, increased efficiency, and the emergence of innovative solutions like bifacial and perovskite solar cells. Through a comprehensive review of numerical data and case studies, the findings reveal that global solar capacity reached approximately 1,059 gigawatts by 2021, showcasing rapid adoption and substantial reductions in greenhouse gas emissions. The paper also discusses the economic benefits of solar energy, including job creation and cost savings for households, while underscoring the importance of supportive policies and regulatory frameworks in promoting solar deployment. The integration of solar energy with energy storage systems is identified as a crucial development for enhancing reliability and addressing intermittency challenges. Future directions include the continued advancement of solar technology and the need for comprehensive policies that encourage investment in renewable energy. This study underscores the potential of solar energy to contribute significantly to sustainable development and climate change mitigation, positioning it as a key player in achieving global energy transition goals.